2014
DOI: 10.1188/14.onf.311-321
|View full text |Cite
|
Sign up to set email alerts
|

Communication Behaviors and Patient and Caregiver Emotional Concerns: A Description of Home Hospice Communication

Abstract: Home hospice provides a venue to examine nurse communication behaviors used to elicit and respond to patient and caregiver distress. These strategies could be taught to nurses who encounter patient distress less frequently or are less comfortable with emotional conversations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…When cancer patients are told that their disease is terminal and referral to HPC is necessary, they develop an array of more complex emotional states (Kubler-Ross, Wessler, & Avioli, 1972;Yun et al, 2010). Patients and caregivers often express concerns regarding psychological and physical issues, and frequently talk about causes of distress (Clayton, Reblin, Carlisle, & Ellington, 2014 (Chochinov et al, 2009). Patients and caregivers often express concerns regarding psychological and physical issues, and frequently talk about causes of distress (Clayton, Reblin, Carlisle, & Ellington, 2014 (Chochinov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cancer patients are told that their disease is terminal and referral to HPC is necessary, they develop an array of more complex emotional states (Kubler-Ross, Wessler, & Avioli, 1972;Yun et al, 2010). Patients and caregivers often express concerns regarding psychological and physical issues, and frequently talk about causes of distress (Clayton, Reblin, Carlisle, & Ellington, 2014 (Chochinov et al, 2009). Patients and caregivers often express concerns regarding psychological and physical issues, and frequently talk about causes of distress (Clayton, Reblin, Carlisle, & Ellington, 2014 (Chochinov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there can be a wide range of feelings that may include sadness and depression, grief, denial, anger, stress, fear and worry, guilt and regret, and loneliness (Yun et al, 2010). Patients and caregivers often express concerns regarding psychological and physical issues, and frequently talk about causes of distress (Clayton, Reblin, Carlisle, & Ellington, 2014 The present study indicated that 22 days or more of HPC for a terminal cancer patient can lead to improved existential well-being, better preparation for death and a better sense of control over the future. Patients affected by cancer encounter spiritual distress at the EOL (Chochinov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Research is also needed to examine the family dynamics; their impact on the communication among patients, family members, and providers; and the benefits, challenges, and strategies to facilitate family involvement to enhance healthcare outcomes. Finally, this study focused on the communication behaviors of patients and family members, which may have simplified the interpersonal process in which providers played an extremely important role in eliciting patient and family concerns [49]. Future research is needed to explore the complexity of the communication interactions during treatment consultation visits.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Oncology Nursing Forum, Clayton, Reblin, Carlisle, and Ellington (2014) used the Roter Interaction Analysis System (RIAS) to identify and describe communication behaviors used by hospice nurses when eliciting and addressing patient and caregiver concerns. The RIAS is a coding system that does not transcribe recordings, but performs coding by listening and applying codes for each utterance or thought expressed by a single person, both negative and positive.…”
Section: Applicationmentioning
confidence: 99%